2016
DOI: 10.1371/journal.pone.0155591
|View full text |Cite
|
Sign up to set email alerts
|

Can Native T1 Mapping Differentiate between Healthy and Diffuse Diseased Myocardium in Clinical Routine Cardiac MR Imaging?

Abstract: ObjectivesT1 mapping allows quantitative myocardial assessment, but its value in clinical routine remains unclear. We investigated, whether the average native myocardial T1 value can be used as a diagnostic classifier between healthy and diffuse diseased myocardium.MethodsNative T1 mapping was performed in 54 persons with healthy hearts and in 150 patients with diffuse myocardial pathologies (coronary artery disease (CAD): n = 76, acute myocarditis: n = 19, convalescent myocarditis: n = 26, hypertrophic cardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 22 publications
1
31
0
Order By: Relevance
“…1. A total of ten studies were included for the HCM group, 17,29-37 nine for DCM, 11,30,33,35,[38][39][40][41][42] twelve in MC, 30,[43][44][45][46][47][48][49][50][51][52][53] five in iron overload, 54-58 six in amyloidosis, 32,[59][60][61][62][63] two in Fabry disease, 64,65 ten in HT, 13,17,34,37,[66][67][68][69][70][71] four in DM, [72][73][74][75] and one in obesity 74 ( Table 1). The field strength is known to influence the T 1 values significantly 65 ; therefore, results from studies performed on a 1.5T or 3T are shown separately, but used as covariant in the meta-regression analysis.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
“…1. A total of ten studies were included for the HCM group, 17,29-37 nine for DCM, 11,30,33,35,[38][39][40][41][42] twelve in MC, 30,[43][44][45][46][47][48][49][50][51][52][53] five in iron overload, 54-58 six in amyloidosis, 32,[59][60][61][62][63] two in Fabry disease, 64,65 ten in HT, 13,17,34,37,[66][67][68][69][70][71] four in DM, [72][73][74][75] and one in obesity 74 ( Table 1). The field strength is known to influence the T 1 values significantly 65 ; therefore, results from studies performed on a 1.5T or 3T are shown separately, but used as covariant in the meta-regression analysis.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
“…Although a growing body of evidence suggests the usefulness of stress echocardiography in SSc‐HD, which is a cheaper and easy method to assess myocardial ischemia, this technique may show some limitations. In fact, both pharmacological stress and exercise stress echocardiography may be difficult in the presence of a poor acoustic window; imaging acquisition, during stress, is more difficult for the greater increase in both heart and respiratory rates, and finally it is strongly operator sensitive, thus, pharmacological stress perfusion CMR may allow the physician to overcome the limitations of echocardiography . However, some limitations regarding pharmacological stress, rest‐perfusion and delayed enhancement CMR should be taken into account, including claustrophobia, the presence of an implant or other metallic object, irregular heartbeat, pregnancy, and the relatively low number of MRI centers equipped for pharmacological stress perfusion CMR …”
Section: Discussionmentioning
confidence: 99%
“…In fact, both pharmacological stress and exercise stress echocardiography may be difficult in the presence of a poor acoustic window; imaging acquisition, during stress, is more difficult for the greater increase in both heart and respiratory rates, and finally it is strongly operator sensitive, 51 thus, pharmacological stress perfusion CMR may allow the physician to overcome the limitations of echocardiography. [52][53][54] However, some limitations regarding pharmacological stress, rest-perfusion and delayed enhancement CMR should be taken into account, including claustrophobia, the presence of an implant or other metallic object, irregular heartbeat, pregnancy, and the relatively low number of MRI centers equipped for pharmacological stress perfusion CMR. [16][17][18] As an alternative method, single-photon emission CT (SPECT) was proposed for the assessment of myocardial perfusion abnormalities during SSc.…”
Section: Discussionmentioning
confidence: 99%
“…The T1 _native value is thus an inherent tissue-specific property and these values have been shown to be highly effective in differentiating healthy myocardium from diffusely diseased tissue. 15 We have previously demonstrated that T1 mapping predicts appropriate ICD therapy in a mixed cohort of ICM and NCM ICD patients at 15-month mean follow-up. 16 It is not clear whether T1 _native remains predictive of VA in the medium to long term in ICD patients and whether the different magnetic resonance imaging (MRI) protocols assessing focal and diffuse fibrosis have specific value for ICM and NCM, respectively.…”
mentioning
confidence: 92%
“…Native T1 mapping (T1 _native ) using CMR allows the quantitative assessment of myocardial tissue in vivo without the administration of contrast and is elevated in the presence of edema, diffuse fibrosis, and myocardial scarring. The T1 _native value is thus an inherent tissue‐specific property and these values have been shown to be highly effective in differentiating healthy myocardium from diffusely diseased tissue . We have previously demonstrated that T1 mapping predicts appropriate ICD therapy in a mixed cohort of ICM and NCM ICD patients at 15‐month mean follow‐up .…”
Section: Introductionmentioning
confidence: 99%